1987
DOI: 10.21273/jashs.112.4.712
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Competition Improves Performance and Reproductive Output of the Common Zucchini Squash Under Field Conditions

Abstract: The objective of this study was to examine the effects of pollen competition on offspring quality in the common zucchini squash (Cucurbita pepo L.). In a controlled field study, we compared the performance of seeds that were produced under conditions of pollen competition (high pollen loads) to seeds produced under conditions of little or no pollen competition (low pollen loads). We found that seeds from high pollen loads were more likely to emerge and emerge more rapidly than seeds from low pollen loads. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Whereas Lima and coauthors [18] observed lower production and quality (germination and vigor) of seeds in 'Caserta' zucchini when using less pollen grains in manual pollination. Davis and coauthors [25] observed that pumpkin seeds produced with a larger amount of pollen grains showed faster germination. Boron is very important to fruit and seed formation process, because it acts in cell walls formation, cell division, pollen grain germination, flowering and fruit formation.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Whereas Lima and coauthors [18] observed lower production and quality (germination and vigor) of seeds in 'Caserta' zucchini when using less pollen grains in manual pollination. Davis and coauthors [25] observed that pumpkin seeds produced with a larger amount of pollen grains showed faster germination. Boron is very important to fruit and seed formation process, because it acts in cell walls formation, cell division, pollen grain germination, flowering and fruit formation.…”
Section: Resultsmentioning
confidence: 98%
“…There are reports that when there is a large amount of pollen grains on the stigma, they compete with each other and the most vigorous prevail in the fertilization of ovules, resulting in more vigorous seeds. Davis and coauthors [25] and Hormaza and Herrero [30] considered that the breeder when using large quantities of pollen grains establish competition capable of selecting the most vigorous ones. Thus, for the breeder, there is the possibility of selecting more vigorous populations only by exposing the female flowers to a large amount of pollen, without the need for large areas, only taking advantage of the intense competition among pollen grains [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cuando el número de granos de polen depositado en un estigma supera el número de óvulos en el ovario puede existir competencia entre los micro gametofitos (teoría de competencia micro gametofítica; Mulcahy y Mulcahy. 1975, McKenna 1986, Davis et al 1987. Tubos polínicos de crecimiento rápido llegan antes a fertilizar los óvulos que tubos de crecimiento lento, y los tubos de crecimiento rápido generan progenie más vigorosa.…”
Section: Discussionunclassified
“…Soon after germination, endogenous gibberellin (GA3 and GA4) concentrations increased in pollen tubes and were positively correlated with fruit growth (Zhang et al, 2010). Researchers Davis et al (1987), Schlichting et al (1990), and Quesada et al (1996) found that variations in pollen load (the number of pollen grains deposited on each stigma) had an impact on not only the number of seeds per fruit but also how quickly the progeny produced by a high pollenload germinated and developed.…”
Section: Introductionmentioning
confidence: 99%